Development of Interactive Multimedia Based on Explanation Text Materials Using Adobe Animate - May Syarah; Mara Untung Ritonga; Syarifah Syarifah (RIRAI Publisher, 2023)
This research is a research and development research on interactive multimedia-based explanatory text that aims to determine the validation, practicality and effectiveness of the product developed. Development of Interactive Multimedia -Based Explanation Text Materials Using the Procedure for Developing ADDIE Model. The ADDIE development model has 5 steps, namely: Analyze, Design, Development, Implementation, and Evaluation (Evaluation). The results showed that effectiveness was obtained based on increased student learning outcomes after pretest and posttest with N-Gain of 0.65 'medium' criteria. In the completed student pretest as many as 7 out of 25 students after using a posttest product and students who completed 22 out of 25 students. Mastery learning with a percentage value of 88% with the 'very good' category. It can be concluded that student learning outcomes increase after using the teaching material for interactive and effective multimedia -based explanatory texts.